Distribution of Leprosy Cases Based on Demographic Characteristics in South Sumatra: Analysis of Provincial Health Profile Data from 2019 to 2023 - Ihsan, Sri Wahyuni; Fauziah, Suci; Inayah, Sitti Zahra; Santri; Pabutung, Scolastika Melshe (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2026)
Background: Leprosy is a chronic infectious disease caused by Mycobacterium leprae that primarily affects the skin, peripheral nerves, and other organs. Inadequate management may result in irreversible physical disability and significant social stigma. Although Indonesia achieved the elimination target in 2000, with a national prevalence of 0.9 per 10,000 population, leprosy remains a public health concern, particularly in developing regions. In South Sumatra Province, the prevalence rate in 2023 was 0.24 per 10,000 population, showing a decline from the previous year; however, case trends over the last five years have fluctuated, peaking in 2019. Globally, the World Health Organization targets leprosy elimination by 2030. Effective control relies on early diagnosis, as well as the capacity and performance of healthcare workers and facilities. Objectives: This study aims to analyze the distribution of leprosy cases in South Sumatra from 2019 to 2023. Methods: A quantitative descriptive design was applied using secondary data from the Provincial Health Profile. Data were analyzed narratively and presented through graphical visualizations. Complementary evaluation of healthcare performance employed a combined cross-sectional and retrospective approach in selected facilities, assessing knowledge, clinical skills, and case management practices. Results: The findings indicate annual fluctuations in both Pausi Basiler and Multibasiler cases. Geographic conditions, healthcare accessibility, and socio-cultural factors contribute to these variations. Conclusion: Despite declining prevalence, transmission persists, particularly reflected in Multibasiler and pediatric cases, highlighting the need for sustained and comprehensive control strategies. Keywords: leprosy, Pausi Basiler, Multibasiler, distribution, children, South Sumatra.